Creep of welded branched pipes - Rayner, Glen (2004)
Creep failure of welds in high-temperature power plant steam piping systems is known to be a potential cause of plant failure. Creep behaviour of plain pipes with circumferential welds and cross-weld specimens have received fairly extensive attention. However, research into the creep behaviour of welded thick-walled branched steam pipes has received less attention. Consequently, this thesis addresses improving the understanding of the creep behaviour for this type of geometry. Numerical and analytical methods are used to assess the creep behaviour of typical power plant branched pipe geometries.